Violet-emitting distributed-feedback laser using a naphtho[2, 1-b:6, 5-b′]difuran derivative. Issue 48 (29th November 2021) - Tsuji, Hayato; Shitomi, Akihiro; Hamaguchi, Naoto; Egawa, Yasunobu; Bonal, Víctor; Boj, Pedro G.; Villalvilla, José M.; Quintana, José A.; Díaz-García, María A.
Abstract : A highly emissive fused furan compound, naphtho[2, 1- b :6, 5- b ′]difuran derivative, has been found to serve as an active material for distributed-feedback lasers. Abstract : A naphtho[2, 1- b :6, 5- b ′]difuran derivative was found to serve as an effective violet-emitting laser dye. It showed amplified spontaneous emission at 413 nm with the threshold of 1.1–2.9 mJ cm −2 using 0.1–0.5 wt% in polystyrene film. Lasing was also demonstrated using all-polymeric distributed-feedback lasers emitting at 411–417 nm with the threshold of 2.0–2.9 mJ cm −2 .